Methods for improving the durability of recycled aggregate concrete: A review - Yuanxun Zheng (Elsevier, 2021)
With increasing global research on the recycling of construction waste, the recycling of waste concrete aggregates has gradually attracted attention. Researches have shown that recycled aggregate (RA) has a certain degree of influence on the mechanical properties and durability of recycled aggregate concrete (RAC) owing to its high water absorption, high porosity, and large number of microcracks. Therefore, how to improve the mechanical properties and durability of RAC is a key issue of concern for scholars. Based on the review of related literature and comprehensive analysis, the reinforcement theories and methods such as self-reinforcement of recycled coarse aggregate (RCA), optimization of preparing technology of RAC, and external spiral constraint of RAC were systematically summarized in this paper. The results indicate that the adherent mortar of RCA can be enhanced by carbonation, and weak acid treatment can effectively remove the old adhesion of RCA, which is economical and environmentally friendly. The denseness of RAC can be improved by adding cementitious materials with volcanic ash effect, and the reduction of microcracks in mortar can be improved by adding fibers. The load-bearing capacity and mechanical properties of RAC are significantly improved by the spiral constraint of materials such as fiber reinforced polymer (FRP) and so on. The optimization of the production process not only improves the quality of RAC, but also enhances the production efficiency. The microstructure analysis of RAC was also summarized in this paper. Moreover, the results of this study can provide a technical reference for research on the mechanical strength and durability of RAC, develop the further research ideas, and promote the application of RAC. Finally, some potential opportunities and development directions have been suggested for future research on the improvement methods of RAC.